Analysis of Student Learning Results on Work and Energy Materials - Marina; Padmi Adika (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research aims to determine student learning outcomes in work and energy subjects at the Jambi City Madrasah Aliyah Laboratory for the 2022/2023 academic year. The type of research that researchers have carried out is descriptive qualitative. The population in this study were students of class X MIPA 1 and class X MIPA 2 at the Madrasah Aliyah Laboratory, Jambi City. The sample in this research was class X MIPA 1, totaling 20 students, using a purposive sampling technique. Researchers collected data using essay questions adjusted to the material work and energy indicators. The research results show that students' learning outcomes in work and energy materials are or are categorized in the Sufficient category.